The effects of infrastructure, process support, marketing assistance, and networking services provided by business incubators on startup survival during COVID-19: A case study on startup founders under DTI IDEA - Francisco, Shiela May K. (Animo Repository, 2023)
Business incubators have been around for decades and their main purpose is to cultivate startups that have potential in the market with their usual service offerings being providing infrastructure, marketing assistance, process support, and networking activities. Most studies show that these services contribute to increasing the survival of startups, however, there are few studies done in the middle of the pandemic where many businesses were shut down. This study aims to address the effects of business incubator services to the survival of startups as well as the effect of each type of service on startups that were newly established during the pandemic. With this, the researchers conducted a case study on the Incubation, Development, and Entrepreneurial Assistance (IDEA) Program of DTI Idea and PhilDev Foundation with a total of 34 startup founders and co-founders under it. Through Pearson Correlation, Linear and Multiple Regression, Durbin-Watson Test and Multicollinearity Statistics, the results show that the four business incubator services, individually and collectively, significantly contribute to the startup survival. These findings bring value to most especially to managers in knowing what to prioritize in order to increase their survival.